Efficient Data Dissemination in Cooperative Multi-RSU Vehicular Ad Hoc Networks (VANETs) - Nawaz Ali, G.G.Md. (2016)
Many safety and non-safety related applications have been envisioned in VANETs. However, efficient data dissemination considering the mobility of vehicle is must for the success of these applications. Although the Road Side Unit (RSU) is a stationary unit, both RSU and vehicle have limited transmission range that restricts to shorter connection time. This endures a higher request drop rate specially at the overloaded RSUs. A cooperative load balancing (CLB) among the RSUs to use their residual bandwidth can be an effective solution to reduce the request drop rate. In this paper, we investigate that considering the remaining delay tolerance of submitted requests and the knowledge of fixed road layout, the performance of the cooperative load balancing system can be further improved significantly. We show that this performance gain comes from serving the requests based on the urgency and the efficient load balancing among the junction-RSUs and edge-RSUs. Based on the observations, we propose an Enhanced CLB (ECLB) approach in this paper. To demonstrate the efficiency of the ECLB approach a number of well-known scheduling algorithms are integrated and an extensive simulation experiments are conducted in the vehicular communication environment that supports the superiority of ECLB over the existing approaches.